2018
DOI: 10.3390/nano9010011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasonic Dispersion Energy on the Preparation of Amorphous SiO2 Nanomaterials for In Vitro Toxicity Testing

Abstract: Synthetic amorphous silica (SAS) constitute a large group of industrial nanomaterials (NM). Based on their different production processes, SAS can be distinguished as precipitated, fumed, gel and colloidal. The biological activity of SAS, e.g., cytotoxicity or inflammatory potential in the lungs is low but has been shown to depend on the particle size, at least for colloidal silica. Therefore, the preparation of suspensions from highly aggregated or agglomerated SAS powder materials is critical. Here we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 69 publications
3
23
0
1
Order By: Relevance
“…This indeed resulted in de-aggregation of SAS but did not yield sizes with substantial differences whatever the energy delivered (≥ 882 J, see Additional file 2: Figure S4). A recent study also showed that different sonication energies used to disperse SAS did not strongly affect the size distribution and hence the biological effects [18]. Therefore, we used a mechanically vortexed suspension (AGGR) to obtain a size distribution different from DE-AGGR.…”
Section: Discussionmentioning
confidence: 99%
“…This indeed resulted in de-aggregation of SAS but did not yield sizes with substantial differences whatever the energy delivered (≥ 882 J, see Additional file 2: Figure S4). A recent study also showed that different sonication energies used to disperse SAS did not strongly affect the size distribution and hence the biological effects [18]. Therefore, we used a mechanically vortexed suspension (AGGR) to obtain a size distribution different from DE-AGGR.…”
Section: Discussionmentioning
confidence: 99%
“…To describe and predict the bioactivity of the multitude of SAS, in vitro assays using different cell types and incubation conditions have been published [ 13 , 14 , 15 , 16 , 17 ]. Recently, the effects of SAS from all major production processes were tested using rat alveolar macrophages (NR8383) in vitro [ 18 ]. A major finding was that SAS, irrespective of the production method, elicit highly uniform responses, e.g., with respect to the release of lactate dehydrogenase (LDH), glucuronidase (GLU), tumour necrosis factor alpha (TNFα) or induction of H 2 O 2 release [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of SAS from all major production processes were tested using rat alveolar macrophages (NR8383) in vitro [ 18 ]. A major finding was that SAS, irrespective of the production method, elicit highly uniform responses, e.g., with respect to the release of lactate dehydrogenase (LDH), glucuronidase (GLU), tumour necrosis factor alpha (TNFα) or induction of H 2 O 2 release [ 18 ]. In these experiments, cells were exposed to SAS under protein-free standard conditions, i.e., in the absence of serum proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Food grade silicon dioxide (SiO 2 ) has been known to have very low toxicity with a NOAEL (no observed adverse effect level) of over 2000 mg/kg when ingested orally [ 3 , 4 ]. However, various environmental factors such as heating, pH change, and potential interaction with food ingredients imposed during food processing may cause undesirable alterations in the physicochemical properties of food additive SiO 2 present in processed food, which may lead to changes in its toxicity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In fact, studies have shown that the particle size is an important parameter that determines the penetrating nature of SiO 2 in biological tissues, which may also increase its toxicity [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, various environmental factors such as heating, pH change, and potential interaction with food ingredients imposed during food processing may cause undesirable alterations in the physicochemical properties of food additive SiO 2 present in processed food, which may lead to changes in its toxicity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In fact, studies have shown that the particle size is an important parameter that determines the penetrating nature of SiO 2 in biological tissues, which may also increase its toxicity [ 10 , 12 ]. The growing concerns regarding the potential toxicity of nanoscale food additive SiO 2 have necessitated the effective means of extracting intrinsic forms of SiO 2 from a range of processed food for the analysis of its physicochemical properties and safety.…”
Section: Introductionmentioning
confidence: 99%